OPTIMIZATION OF TRIANGLE’S TRIANGULATION - Казмерчук, Анатолій Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The problem of triangulation triangle with straight lines is examined. Estimates for the number of triangles are obtained. We found the minimum number of straight lines in the division that the ratio of the number of triangles to the number of straight lines is not less than the given number.